Improving EFL Speaking of Guides at The Aceh Tsunami Museum - Cut Intan Damayanti (English Education Journal, 2018)
This research was aimed at finding out the English language proficiency of the local guides at the Aceh Tsunami Museum and the difficulties faced by them in communicating with English speaking visitors. The research design used in this study was a qualitative descriptive method and in order to collect data, the writer used a test as an instrument. The test was an interview: asking for their opinion about the philosophy of the Aceh Tsunami Museum and asking for information about the collections in the museum, in which the writer served as the active interviewer in collecting the data. The respondents in this research were 13 local guides from the Aceh Tsunami Museum. The interview test was aimed at gathering more data and information needed from these guides  on their English language proficiency and the difficulties faced by them in communicating with tourist visitors. In addition, the writer recorded and took pictures of all the activities done during the interviews. Based on the research results, only one guide from the 13 was in the excellent category for all speaking aspects (excellent in grammar, vocabulary, comprehension, fluency, and pronunciation). While the others were in the categories of very good, good, and fair enough. Mostly, the difficulties faced by the guides at the Aceh Tsunami Museum in speaking English were about expressing ideas verbally, lack of vocabulary, lack of knowledge about grammar and collocations, and poor pronunciation all of which made them not confident to speak English and this was mostly due to lack of motivation, lack of training and even lack of practice speaking with tourist visitors.